2014
DOI: 10.1158/2326-6066.cir-14-0035
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Personalized Peptide Vaccination for Previously Treated Advanced Colorectal Cancer

Abstract: The prognosis of advanced colorectal cancer (aCRC) remains poor, and development of new therapeutic approaches, including immunotherapy, is needed urgently. Herein we report on our phase II study of personalized peptide vaccination (PPV) in 60 previously treated patients with aCRC, who had failed at least one regimen of standard chemotherapy and/or targeted therapy. For PPV, a maximum of four HLA-matched peptides were individually selected from a pool of 31 different peptide candidates based on preexisting hos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 37 publications
8
83
1
Order By: Relevance
“…This supports a possibility that IL6/sIL6R converts the transferred or in vivo activated CD4 þ T cells into dysfunctional T cells in patients with cancer when T-cellmediated immunotherapy such as adoptive T-cell transfer including chimeric antigen receptor-expressing T cells (CAR-T cells) therapy, vaccination with tumor-associated antigenic peptides, or immune checkpoint blockade, were given. Indeed, recent trials demonstrated that the level of IL6 correlated with overall survival rate of patients treated with immunotherapies (39)(40)(41). It is particularly intriguing that following CAR T-cell infusion, the humanized anti-IL6R Ab tocilizumab is widely used to lessen cytokine release syndrome (CRS)-related toxicities (2,42).…”
Section: Discussionmentioning
confidence: 99%
“…This supports a possibility that IL6/sIL6R converts the transferred or in vivo activated CD4 þ T cells into dysfunctional T cells in patients with cancer when T-cellmediated immunotherapy such as adoptive T-cell transfer including chimeric antigen receptor-expressing T cells (CAR-T cells) therapy, vaccination with tumor-associated antigenic peptides, or immune checkpoint blockade, were given. Indeed, recent trials demonstrated that the level of IL6 correlated with overall survival rate of patients treated with immunotherapies (39)(40)(41). It is particularly intriguing that following CAR T-cell infusion, the humanized anti-IL6R Ab tocilizumab is widely used to lessen cytokine release syndrome (CRS)-related toxicities (2,42).…”
Section: Discussionmentioning
confidence: 99%
“…44 To date, peptide-DC therapies are limited to the stimulation of CD8+ cytotoxic responses. 23,[45][46][47][48][49] The problem of inducing CD4+ T cell responses that is also required to treat tumors remains unresolved. 50,51 Therefore, when using lysate/protein/peptide-loaded DCs, the expression duration is limited not only by the affinity of a peptide to a MHC molecule but also by the half-life of a peptide-MHC complex and the turnover of MHC molecules.…”
Section: Peptidesmentioning
confidence: 99%
“…Multiple (two to four) antigens are selected and administered to increase the likelihood of the vaccinated antigens matching those expressed by the tumor cells [68,69]. A series of early phase (phase I and/or phase II) clinical trials of PPV that were conducted for patients with various types of advanced cancers, including CRC, have shown the feasibility of this new approach [69][70][71][72][73][74][75][76][77][78][79][80]. For example, we have recently demonstrated that the patients treated with PPV showed a significantly longer overall survival (OS) than those with standard care and treatment in randomized phase II studies for bladder cancer and prostate cancer [72,73].…”
Section: Rationale Of Ppvmentioning
confidence: 99%
“…More recently, a phase II study of PPV was conducted to examine the feasibility of PPV in previously treated CRC patients, who had failed at least one regimen of standard chemotherapies and/or targeted therapies [79]. During PPV, most of the patients (82%) were treated in combination with chemotherapies and/or targeted therapies.…”
Section: Clinical Trials Of Ppv For Crc Patientsmentioning
confidence: 99%